COST ESCALATION ANALYSIS (PRICE ADJUSTMENT) ON MULTI YEARS INFRASTRUCTURE PROJECTS (PLUAL YEARS) - Anisa Meiyanur; Diah Ayu Restuti Wulandari (NAROTAMA UNIVERSITY, Indonesia, 2022)
The Kalimati Long Storage Project for Raw Water is one of the projects implemented in Sidoarjo Regency under the supervision of the Brantas River Basin which is a Multiyears project. Where project activities last for 2 (two) years or approximately 720 working days. Multiyears (Multiple Years) projects have risks in the implementation process. One of the risks in the Multiyears project is the adjustment of the unit price of contract components which include building materials, labor, and equipment to the contract value at the time of the auction. In bidding prices in the tender/auction process, contractors must pay attention to construction costs, overhead and profits. The accuracy of the construction cost estimation is in accordance with the project stages from planning, design to final estimation at the time of project completion. The guidelines in this study use the escalation calculation that has been regulated based on Presidential Regulation Number 70 of 2012 article 92 which has been stated in the project agreement contract. This research was conducted on a multi-year project based on government regulations and literature. From the analysis of the cost escalation calculation for October 2018 – December 2019 there is a weight difference of 6.74% from the escalation value. The results of the calculation of the escalation value obtained a value of Rp. 13,457,629.000.00. While the value of the increase in costs of Rp. 199,732,279,557.48 with a total payment of Rp. 357,235,377,870.00. There is a weight difference of 6.75% from the escalation value. The results of the calculation of the escalation value obtained a value of Rp. 13,485.882,216.22. While the value of the increase in costs of Rp. 199,732,279,557.48 with a total payment of Rp. 357,263,630,870.00